General Studies for Civil Services Preliminary Examination General Studies Paper I 2020: Also useful for State Public Service Commission Examination (Mc Graw Hill, 2020)
Thoroughly updated and comprehensive study material with a dedicated focus on the latest syllabus prescribed by the UPSC for preliminary examination. This edition has undergone immense structural changes, making the content more precise and examination centric by weeding out redundant information.